2000
DOI: 10.1093/emboj/19.22.6162
|View full text |Cite
|
Sign up to set email alerts
|

Direct transcriptional control of the Dpp target omb by the DNA binding protein Brinker

Abstract: The gradient morphogen Decapentaplegic (Dpp) organizes pattern by inducing the transcription of different target genes at distinct threshold concentrations during Drosophila development. An important, albeit indirect, mode by which Dpp controls the spatial extent of its targets is via the graded downregulation of brinker, whose product in turn negatively regulates the expression of these targets. Here we report the molecular dissection of the cis-regulatory sequences of optomotor-blind (omb), a Dpp target gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 46 publications
3
90
0
1
Order By: Relevance
“…Prepared proteins were incubated on ice for 30 minutes with ~50,000 c.p.m. of labeled probes in binding buffers as described (Hepker et al, 1999;Kim et al, 1997;Sivasankaran et al, 2000). In some samples, unlabelled wild-type oligos (specific competitor) and mutant oligos (nonspecific competitor) were included.…”
Section: Protein Preparations and Gel Mobility Shift Assaysmentioning
confidence: 99%
See 3 more Smart Citations
“…Prepared proteins were incubated on ice for 30 minutes with ~50,000 c.p.m. of labeled probes in binding buffers as described (Hepker et al, 1999;Kim et al, 1997;Sivasankaran et al, 2000). In some samples, unlabelled wild-type oligos (specific competitor) and mutant oligos (nonspecific competitor) were included.…”
Section: Protein Preparations and Gel Mobility Shift Assaysmentioning
confidence: 99%
“…A potential candidate, the transcriptional repressor of Dpp target genes, Brk (Campbell and Tomlinson, 1999;Jazwinska et al, 1999;Kirkpatrick et al, 2001;Minami et al, 1999;Rushlow et al, 2001;Saller and Bienz, 2001;Sivasankaran et al, 2000;Zhang et al, 2001), is suggested by evidence indicating that Dpp is required to override REPE function. In the wing and leg imaginal discs, brk expression is repressed by and is roughly reciprocal to Dpp signaling.…”
Section: Brinker Opposes Hh Signaling Through the D-h Enhancermentioning
confidence: 99%
See 2 more Smart Citations
“…omb is a Drosophila T-box gene positively regulated by Dpp [48,55] and is expressed in a broad region in the middle of the wing disc (Figure 1I). X-Gal staining was used to monitor the expression levels of omb-lacZ in wing discs, the enhancer trap lines for omb.…”
Section: Resultsmentioning
confidence: 99%